New material of Pepesuchus (Crocodyliformes; Mesoeucrocodylia) from the Bauru Group: implications about its phylogeny and the age of the Adamantina Formation - Cezar Geroto, Caio Fabricio [UNESP]; Bertini, Reinaldo J. [UNESP] (Oxford Univ Press, 2019)
The Bauru Group has three crocodyliform taxa: Itasuchus, Pepesuchus and Barreirosuchus. Within these taxa, the skulls of Itasuchus jesuinoi and Barreirosuchus franciscoi are fragmentary and have no described postcranial material, hindering the comparison with other specimens with known taxonomic positions. Thus, the taxonomic placement of I. jesuinoi and B. franciscoi remains unsolved. Additionally, although the Marilia Formation has been dated to the Maastrichtian Age, the chronology of the Adamantina Formation is up for debate. New material found in the Adamantina Formation, referred to Pepesuchus, is described. Phylogenetic analysis returned a supported clade composed of Itasuchus, Pepesuchus and Barreirosuchus, here named Pepesuchinae. Pepesuchinae is a sister clade to Peirosaurinae, a clade grouping Peirosaurus, Uberabasuchus, Montealtosuchus and Hamadasuchus. The calibrated cladogram dates the origin of the Bauru Group to the early Santonian, and the morphological similarity between the taxa from the Adamantina and Marilia formations makes it possible to infer a Campanian-Maastrichtian age for the Adamantina Formation.
Keywords: alpha taxonomy; Cretaceous; Crocodylomorpha; Itasuchus; Peirosauridae; Peirosaurus; phylogenetic systematics; Pepesuchus; Pepesuchinae; Zyphosuchia